2019
DOI: 10.1186/s13104-019-4046-1
|View full text |Cite
|
Sign up to set email alerts
|

Plant growth-promoting rhizobacterium Pseudomonas PS01 induces salt tolerance in Arabidopsis thaliana

Abstract: ObjectivesPlant growth-promoting rhizobacteria (PGPR) may contribute to sustainable crop production by improving plant growth and/or plant tolerance to abiotic stresses. Soil salinity, which limits the productivity of crop plants, is one of the major concerns of modern agriculture, especially in countries heavily affected by climate change as Vietnam. Currently, only a few reports have studied local PGPR isolated in Vietnam, particular Pseudomonas. Therefore, our study aimed to isolate and identify a region-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 117 publications
(70 citation statements)
references
References 37 publications
3
65
0
2
Order By: Relevance
“…The results showed that after 2 days of incubation, a higher rate of germination was observed in bacteria coated seeds (51.5%), compared to uncoated seeds (31.3%) (n = 100) ( Figure S3). Previously, we reported the improvement of Arabidopsis germination rate in salt stress conditions by PS01 [45]. Here, we showed that after 30 days of growth in green-house conditions, inoculation of bacteria resulted in an increase in shoot and root dry weight by 1.4 fold and 2.2 fold, respectively (Figure 11a,b).…”
Section: Potential Of Ps01 When Applied On Zea Mayssupporting
confidence: 53%
See 4 more Smart Citations
“…The results showed that after 2 days of incubation, a higher rate of germination was observed in bacteria coated seeds (51.5%), compared to uncoated seeds (31.3%) (n = 100) ( Figure S3). Previously, we reported the improvement of Arabidopsis germination rate in salt stress conditions by PS01 [45]. Here, we showed that after 30 days of growth in green-house conditions, inoculation of bacteria resulted in an increase in shoot and root dry weight by 1.4 fold and 2.2 fold, respectively (Figure 11a,b).…”
Section: Potential Of Ps01 When Applied On Zea Mayssupporting
confidence: 53%
“…In the previous studies, we found that Pseudomonas strain PS01 could enhance plant growth in saline conditions, whereas Pseudomonas strains P112 and P113 (coded as PS02 and PS03 in this study) enhanced plant growth in normal conditions [35,45]. In this study, we evaluate plant growth-promoting (PGP) traits of these strains and 17 other strains which were isolated from the rhizosphere and rhizoplane of various crop plants.…”
Section: Plant Growth Promoting Characterization Of Bacteriamentioning
confidence: 88%
See 3 more Smart Citations